Highly stable Pd2+ species anchoring on ethylenediamine-grafted-MIL-101(Cr) as a robust oxidation catalyst - Nuttapong Makmeesub; Chonlada Ritvirulh; Kittisak Choojun; Suchinda Sattayaporn; Daniel E. Resasco; Tawan Sooknoi (Catalysis Science & Technology, 2022)
The strong interaction between Pd 2+ and ethylenediamine (en), within the confinement of MIL-101(Cr), effectively prevented the reduction of Pd 2+ by the feed and minimized leaching of the active Pd 2+ species under oxidizing and acidic conditions.
Keywords: Metal-Organic Frameworks: Synthesis and Applications; Catalytic Processes in Materials Science; Chemical Synthesis and Reactions